The Role of Lack of Integrity as a Moderator of the Fraud Hexagone Influence on Potential Financial Statement Fraud - Yunisari, Anisa; Evana, Einde; Metalia, Mega (Journal of Asian Multicultural Research for Economy and Management Study, 2024)
This study uses quantitative methods to analyze the potential for financial statement fraud in banking companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2022 period. Secondary data from the annual reports of banking companies were used in the study. Data analysis methods include descriptive statistics and logistic regression. The results of the analysis show that most banking companies are not involved in financial statement fraud. Factors such as financial targets, CEO turnover, ineffective monitoring, and political connections have a significant effect on the potential for fraud. Nagelkerke's coefficient of determination suggests that the independent variable can account for about 54.8% of the variability in financial statement fraud. The significance test partially shows that all independent variables have a significant influence on the potential for financial statement fraud.